Strategi pengembangan ekowisata pegunungan di Kabupaten Natuna Provinsi Kepulauan Riau - Said Muhammad Qadry; Zulfan Saam; Dessy Yoswaty (Pelantar Press, 2017)
This research aims to analyze the tourist attractions, amenitas and accessibility assuport ecotourism mountains on Mount Ranai as well as reviewing and formulating development strategies of ecotourism in mountainous area of Mount Ranai. Data retrieval is done by survey method with descriptive qualitative analysis and SWOT analysis. The results of this study indicate the condition of the Attractions found in the region of Mount Ranai is very diverse and is unique so it is potentially exploited as tourist attractions. While amenitas and accessibility is already quite sufficient to support the development of ecotourism mountains. Government’s role is indispensable in the development of ecotourism is mountainous area of Mount Ranai. As for the effort that should involve the parties such as related organizations pertaining to the environment and related agencies. On the other hand, the efforts of the utilization potential of natural resources in a friendly with the concept of ecotourism was necessary in an effort to maintain the raw water source of the local community.